THE TECTONICS STRESS AND STRAIN FIELD MODELING ADJUSTED FOR EVOLUTION OF GEOLOGICAL STRUCTURES (SAILAG INTRUSION, EASTERN SAYAN) - V. N. Voytenko; V. V. Pogorelov; A. O. Yakubovskaya; A. V. Goneger (Геодинамика и тектонофизика, 2015)
The article describes a tectonophysical model showing evolution of structures in the Sailag granodiorite massif in relation to its gold-bearing capacity. The model takes into account the load patterns according to geological data, accumulated deformation, and gravity stresses. This model provides for updating the structural-geological model showing development of the intrusion body and the ore field. Forecasted are destruction patterns in the apical and above-dome parts of the massif  in the intrusion and contraction phase, formation of the long-term shear zone at the steeply dipping slope of the intrusion body, and subvertical fractures associated with the long-term shear zone and vertical mechanical ‘layering’ of the intrusive body.